MACE and VTE across upadacitinib clinical trial programmes in rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis - Peter Nash; Iain B McInnes; Ernest Choy; Jeffrey R Curtis; Eduardo Mysler; Christina Charles-Schoeman; Nasser Khan; Kunihiro Yamaoka; Ralph Lippe; Hannah Palac; Anna K Shmagel; Jessica Suboticki (RMD Open, 2023)
Objectives To provide an integrated analysis of major adverse cardiovascular events (MACEs) and events of venous thromboembolism (VTE) and associated risk factors across rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS) phase 2b/3 upadacitinib clinical programmes.Methods Data were analysed and summarised from clinical trials of RA, PsA and AS treated with upadacitinib 15 mg once daily (QD) and 30 mg QD (as of 30 June 2021). Data from adalimumab (RA and PsA) and methotrexate (RA) arms were included as comparators. Adjudicated MACEs and VTE events were presented as exposure-adjusted rates per 100 patient-years (E/100 PY). Univariable Cox proportional hazard regression analyses assessed potential associations of risk factors for MACE and VTE.Results In total, 4298 patients received upadacitinib 15 mg (RA n=3209, PsA n=907 and AS n=182) and 2125 patients received upadacitinib 30 mg (RA n=1204 and PsA n=921). In patients with RA and PsA, rates of MACE (0.3–0.6 E/100 PY) and VTE (0.2–0.4 E/100 PY) were similar across upadacitinib doses; in patients with AS, no MACEs and one VTE event occurred. Most patients experiencing MACEs or VTE events had two or more baseline cardiovascular risk factors. Across RA and PsA groups, rates of MACEs and VTE events were similar.Conclusions Rates of MACEs and VTE events with upadacitinib were consistent with previously reported data for patients receiving conventional synthetic and biologic disease-modifying anti-rheumatic drugs and comparable with active comparators adalimumab and methotrexate. Associated patient characteristics are known risk factors for MACEs and VTE events.Trial registration numbers RA (SELECT-NEXT: NCT02675426; SELECT-MONOTHERAPY: NCT02706951; SELECT-BEYOND: NCT02706847; SELECT-COMPARE: NCT02629159; SELECT-EARLY: NCT02706873, SELECT-CHOICE: NCT03086343), PsA (SELECT-PsA 2: NCT03104374; SELECT-PsA 1: NCT03104400), and AS (SELECT-AXIS 1: NCT03178487).